Commission on Cancer CP3R Compliance Rates for Treatment of Patients With Triple Negative and HER2+ Breast Cancer: A National Cancer Database Analysis. Issue 10 (October 2021) - Mohan, Srivarshini C.; Tseng, Joshua; Srour, Marissa; Chung, Alice; Marumoto, Ashley; Angarita, Stephanie; Giuliano, Armando E.; Amersi, Farin
Background: Cancer Program Practice Profile Reports (CP3R) metrics were released by the Commission on Cancer to provide standards for high-quality care. One metric is the recommendation of combination chemotherapy or chemo-immunotherapy (CIT) within 120 days of diagnosis for women under 70 with AJCC T1cN0M0 or Stage IB-III HER2+ or hormone receptor negative breast cancer ([Multi-agent chemotherapy] MAC). Our study assesses national concordance rates for MAC and CIT. Methods: The National Cancer Database was queried from 2004-2014. Results: 122, 045 patients met criteria, of whom treatment for 101, 800 (83.4%) patients was concordant with MAC and CIT. Treatment concordance increased from 75.7% in 2004 to 89.5% in 2014. For HER2+ patients, use of CIT treatment downtrended with progression of pathological stage, from 70.1% (stage I) to 58.1% (stage III). Mean overall survival of patients whose treatment was concordant with MAC and CIT was longer than that of patients who were non-concordant (146.6 vs 143.8 months, P <.01). On Cox regression, there was a survival benefit for concordant patients who were treated at academic hospitals (HR .89, 95% CI 0.802-.976) and had private insurance (HR .76, 95% CI 0.65-.89). Conclusion: Compliance with MAC and CIT has improved over the past decade and is associated with a significant improvement in overall survival.